( − )-Arctigenin as a lead compound for anticancer agent - Gui-Rong Chen; Hong-Fu Li; De-Qiang Dou; Yu-Bin Xu; Hong-Shuai Jiang; Fu-Rui Li; Ting-Guo Kang (Natural Product Research, 2013)

Preparation and Characteristics of Sugarcane Low Alcoholic Drink by Submerged Alcoholic Fermentation - Gan-Lin Chen; Feng-Jin Zheng; Bo Lin; Tian-Shun Wang; Yang-Rui Li (Sugar Tech, 2013)

Spectrin: Structure, function and disease - Rui Zhang; ChenYu Zhang; Qi Zhao; DongHai Li (Science China Life Sciences, 2013)

Molecular Cloning and Transcriptional Analysis of the Putative AGAMOUS Homolog AcAG in Onion (Allium cepa) - Hong-You Li; Rui Zhao; Chan Wang; Li-Ying Zhang; Hong Zhao; Yong-Qin Wang (Plant Molecular Biology Reporter, 2013)

Wheat gene TaS3 contributes to powdery mildew susceptibility - Shaohui Li; Rui Ji; Robert Dudler; Mingli Yong; Qide Deng; Zhengyi Wang; Dongwei Hu (Plant Cell Reports, 2013)

Antidepressant-like effects and memory enhancement of a herbal formula in mice exposed to chronic mild stress - Xiu-Ping Sun; Si-Di Li; Zhe Shi; Teng-Fei Li; Rui-Le Pan; Qi Chang; Chuan Qin; Xin-Min Liu (Neuroscience Bulletin, 2013)

Y chromosome diversity and paternal origin of Chinese cattle - Ran Li; Wen-Mei Xie; Zhen-Hua Chang; Shao-Qiang Wang; Rui-Hua Dang; Xian-Yong Lan; Hong Chen; Chu-Zhao Lei (Molecular Biology Reports, 2013)

The N-glycoform of sRAGE is the key determinant for its therapeutic efficacy to attenuate injury-elicited arterial inflammation and neointimal growth - Hyun-Jin Tae; Ji Min Kim; Sungha Park; Noboru Tomiya; Geng Li; Wen Wei; Natalia Petrashevskaya; Ismayil Ahmet; John Pang; Stefanie Cruschwitz; Rebecca A. Riebe; Yinghua Zhang; et al. (Journal of Molecular Medicine, 2013)

Surfactin-Induced Apoptosis Through ROS–ERS–Ca2+-ERK Pathways in HepG2 Cells - Chun-ling Wang; Chuan Liu; Li-li Niu; Li-rui Wang; Li-hua Hou; Xiao-hong Cao (Cell Biochemistry and Biophysics, 2013)

Coralslurrinella hongkonensis gen. nov., sp. nov., a novel bacterium in the family Psychromonadaceae, isolated from the coral Platygyra carnosus - Yanxia Li; Yuki Chan; Yingnan Fu; Rui Zhang; Jill M. Y. Chiu (Antonie van Leeuwenhoek, 2013)

Characterization of microRNA expression profiles in 3T3-L1 adipocytes overexpressing C10orf116 - Jie Qiu; Xiao-guang Zhou; Xiao-yu Zhou; Chun Zhu; Chun-mei Shi; Chen-bo Ji; Rui Cheng; Yong Li; Xi-rong Guo (Molecular Biology Reports, 2013)

Wip1 Phosphatase Involved in Lipopolysaccharide-Induced Neuroinflammation - Xiang Tan; Jingjing Zhang; Wei Jin; Lei Li; Wei Xu; Heyi Zheng; Ying Rui; Kaifu Ke; Ranran Zhou; Maohong Cao; Yongjin Pan (Journal of Molecular Neuroscience, 2013)

Correlation of Nr4a2 Expression with the Neuron Progenitors in Adult Zebrafish Brain - Sheng Chen; Guang Rui Luo; Ting Li; Ting Xi Liu; Weidong Le (Journal of Molecular Neuroscience, 2013)

Elevated risk of opportunistic viral infection in patients with Crohn’s disease during biological therapies: a meta analysis of randomized controlled trials - Xiaobing Wang; Feng Zhou; Junzhang Zhao; Rui Zhou; Meifang Huang; Jin Li; Wei Wang; Shufang Xu; Bing Xia (European Journal of Clinical Pharmacology, 2013)

Effects of the Conversion of Native Vegetation to Farmlands on Soil Microarthropod Biodiversity and Ecosystem Functioning in a Desert Oasis - Feng-Rui Li; Qi Feng; Ji-Liang Liu; Te-Sheng Sun; Wei Ren; Zhen-Huan Guan (Ecosystems, 2013)

Screening of Actinobacillus pleuropneumoniae LuxS Inhibitors - Lu Li; Lili Sun; Yunfeng Song; Xinjuan Wu; Xuan Zhou; Ziduo Liu; Rui Zhou (Current Microbiology, 2013)

A Three-Dimensional Finite Element Model for Biomechanical Analysis of the Hip - Guang-Xing Chen; Liu Yang; Kai Li; Rui He; Bin Yang; Yan Zhan; Zhi-Jun Wang; Bing-Nin Yu; Zhe Jian (Cell Biochemistry and Biophysics, 2013)

Effect of sulphate nutrition on arsenic translocation and photosynthesis of rice seedlings - Rui Song; Chen-Yun Zhao; Juan Liu; Jing Zhang; Yan-Xiu Du; Jun-Zhou Li; Hong-Zheng Sun; Hong-Bing Zhao; Quan-Zhi Zhao (Acta Physiologiae Plantarum, 2013)

Transcriptome profiling and digital gene expression analysis of Nile tilapia (Oreochromis niloticus) infected by Streptococcus agalactiae - Rui Zhang; Li-li Zhang; Xing Ye; Yuan-yuan Tian; Cheng-fei Sun; Mai-xin Lu; Jun-jie Bai (Molecular Biology Reports, 2013)

miR-155 inhibits oxidized low-density lipoprotein-induced apoptosis of RAW264.7 cells - Guo-fu Zhu; Li-xia Yang; Rui-wei Guo; Hong Liu; Yan-kun Shi; Hong Wang; Jin-shan Ye; Zhi-hua Yang; Xing Liang (Molecular and Cellular Biochemistry, 2013)

Association of Endothelin-converting Enzyme-1b C-338A Polymorphism with Increased Risk of Ischemic Stroke in Chinese Han Population - Rui Li; Min Cui; Jin Zhao; Mingming Yu; Zegang Ying; Shiming Zhou; Huadong Zhou (Journal of Molecular Neuroscience, 2013)

Hemoglobin-Induced Nitric Oxide Synthase Overexpression and Nitric Oxide Production Contribute to Blood–Brain Barrier Disruption in the Rat - Shuo Yang; Yizhao Chen; Xinqing Deng; Weiping Jiang; Bing Li; Zhenghao Fu; Mouxuan Du; Rui Ding (Journal of Molecular Neuroscience, 2013)

Up-regulation of SGTB is associated with neuronal apoptosis after neuroinflammation induced by lipopolysaccharide - Maohong Cao; Wei Xu; Jian Yu; Heyi Zheng; Xiang Tan; Lei Li; Ying Rui; Guangfei Xu; Gang Cui; Jian Xu; Jianhua Cao; Tao Tao; et al. (Journal of Molecular Histology, 2013)

Up-regulated expression of Bnip3L after intracerebral hemorrhage in adult rats - Ying Rui; Kaifu Ke; Lei Li; Heyi Zheng; Wei Xu; Xiang Tan; Jianhua Cao; Xiaoyan Wu; Gang Cui; Guangwei Zhao; Yilu Gao; Maohong Cao (Journal of Molecular Histology, 2013)

Characterizing the microbial culprit of white spot disease of the conchocelis stage of Porphyra yezoensis (Bangiales, Rhodophyta) - Xiangyu Guan; Jinbo Li; Zhe Zhang; Fuchao Li; Rui Yang; Peng Jiang; Song Qin (Journal of Applied Phycology, 2013)

Regulation of phenylalanine ammonia-lyase (PAL) gene family in wood forming tissue of Populus trichocarpa - Rui Shi; Christopher M. Shuford; Jack P. Wang; Ying-Hsuan Sun; Zhichang Yang; Hsi-Chuan Chen; Sermsawat Tunlaya-Anukit; Quanzi Li; Jie Liu; David C. Muddiman; Ronald R. Sederoff; Vincent L. Chiang (Planta, 2013)

Cellular boron allocation and pectin composition in two citrus rootstock seedlings differing in boron-deficiency response - Gui-Dong Liu; Rui-Dong Wang; Lei-Chao Liu; Li-Shu Wu; Cun-Cang Jiang (Plant and Soil, 2013)

Potato leafroll virus (PLRV) and Potato virus Y (PVY) influence vegetative growth, physiological metabolism, and microtuber production of in vitro-grown shoots of potato (Solanum tuberosum L.) - Jing-Wei Li; Biao Wang; Xiao-Ming Song; Ren-Rui Wang; Long Chen; Hao Zhang; Zhi-Bo Zhang; Qiao-Chun Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2013)

CTLA-4 polymorphisms and systemic lupus erythematosus (SLE): a meta-analysis - Jin-Xia Zhai; Li-Wei Zou; Zhao-Xiang Zhang; Wen-Jing Fan; Han-Yong Wang; Ting Liu; Zheng Ren; Rui-Xue Dai; Dongqing Ye (Molecular Biology Reports, 2013)

Increased Expression of Small Heat Shock Protein αB-crystallin After Intracerebral Hemorrhage in Adult Rats - Kaifu Ke; Lei Li; Ying Rui; Heyi Zheng; Xiang Tan; Wei Xu; Jianhua Cao; Jian Xu; Gang Cui; Guangfei Xu; Maohong Cao (Journal of Molecular Neuroscience, 2013)

Magma mixing revealed from in situ zircon U–Pb–Hf isotope analysis of the Muhuguan granitoid pluton, eastern Qinling Orogen, China: implications for late Mesozoic tectonic evolution - Rui Liu; Jian-Wei Li; Shi-Jian Bi; Hao Hu; Mi Chen (International Journal of Earth Sciences, 2013)

Membrane Damage Induced by Supercritical Carbon Dioxide in Rhodotorula mucilaginosa - Jun Li; Aiying Wang; Fengmei Zhu; Rui Xu; Xiao Song Hu (Indian Journal of Microbiology, 2013)

Arm–eye coordination test to objectively quantify motor performance and muscles activation in persons after stroke undergoing robot-aided rehabilitation training: a pilot study - Rong Song; Kai-Yu Tong; Xiaoling Hu; Le Li; Rui Sun (Experimental Brain Research, 2013)

In vitro mutagenesis and directed screening for salt-tolerant mutants in peanut - Ming-Xia Zhao; Hai-Yan Sun; Rui-Rui Ji; Xiao-Hui Hu; Jiong-Ming Sui; Li-Xian Qiao; Jing Chen; Jing-Shan Wang (Euphytica, 2013)

Wave equation tomographic velocity inversion method based on the Born/Rytov approximation - Kai Zhang; Zheng Yin; Zhen-Chun Li; Yong-Rui Chen (Applied Geophysics, 2013)

Activating transcription factor 4 is involved in endoplasmic reticulum stress-mediated apoptosis contributing to vascular calcification - Xiao-Hui Duan; Jin-Rui Chang; Jing Zhang; Bao-Hong Zhang; Yu-Lin Li; Xu Teng; Yi Zhu; Jie Du; Chao-Shu Tang; Yong-Fen Qi (Apoptosis, 2013)

Vulcaniibacterium tengchongense gen. nov., sp. nov. isolated from a geothermally heated soil sample, and reclassification of Lysobacter thermophilus Wei et al. 2012 as Vulcaniibacterium thermophilum comb. nov. - Tian-Tian Yu; En-Min Zhou; Yi-Rui Yin; Ji-Cheng Yao; Hong Ming; Lei Dong; Shuai Li; Guo-Xing Nie; Wen-Jun Li (Antonie van Leeuwenhoek, 2013)

Litorilituus sediminis gen. nov. sp. nov., isolated from coastal sediment of an amphioxus breeding zone in Qingdao, China - Yan Wang; Rui Zhao; Shiqi Ji; Zhao Li; Tong Yu; Bingyu Li; Xiaochong Shi; Xiao-Hua Zhang (Antonie van Leeuwenhoek, 2013)

Roseovarius marisflavi sp. nov., isolated from an amphioxus breeding zone in the coastal region of the Yellow Sea, China - Zhao Li; Rui Zhao; Shiqi Ji; Xiaochong Shi; Xiao-Hua Zhang (Antonie van Leeuwenhoek, 2013)

Genome-wide Analysis of the Distribution of AP2/ERF Transcription Factors Reveals Duplication and Elucidates their Potential Function in Chinese Cabbage (Brassica rapa ssp. pekinensis) - Meng-Yao Li; Feng Wang; Qian Jiang; Rui Li; Jing Ma; Ai-Sheng Xiong (Plant Molecular Biology Reporter, 2013)

Molecular Cloning and Expression Analysis of Nine ThTrx Genes in Tamarix hispida - Li Hui-yu; Ning Kun; Song Xin; Wang Zi-jia; Liu Gui-feng; Jiang Jing; Zhang Rui-ping; Li Kai-long (Plant Molecular Biology Reporter, 2013)

Valproic acid reduces autophagy and promotes functional recovery after spinal cord injury in rats - Hai-Hu Hao; Li Wang; Zhi-Jian Guo; Lang Bai; Rui-Ping Zhang; Wei-Bing Shuang; Yi-Jia Jia; Jie Wang; Xiao-Yu Li; Qiang Liu (Neuroscience Bulletin, 2013)

Screening and test of CD40 related signal transduction pathway in AGS cells and construction of gene silencing vector - Rui Li; Wei-Chang Chen; Xue-Qin Pang; Wen-Yan Tian; Wei-Peng Wang; Xue-Guang Zhang (Molecular Biology Reports, 2013)

Clinical and angiographic features associated with coronary collateralization in stable angina patients with chronic total occlusion - Zhen Sun; Ying Shen; Lin Lu; Rui-yan Zhang; Li-jin Pu; Qi Zhang; Zheng-kun Yang; Jian Hu; Qiu-jing Chen; Wei-feng Shen (Journal of Zhejiang University-SCIENCE B, 2013)

The member of high temperature requirement family HtrA2 participates in neuronal apoptosis after intracerebral hemorrhage in adult rats - Huiqing Sun; Lei Li; Feng Zhou; Lin Zhu; Kaifu Ke; Xiang Tan; Wei Xu; Ying Rui; Heyi Zheng; Zhengming Zhou; Huiguang Yang (Journal of Molecular Histology, 2013)

Lack of association between IL-23R gene polymorphisms and systemic lupus erythematosus in a Chinese population - Gui-Mei Chen; Chen-Chen Feng; Qian-Ling Ye; Juan Wang; Han Cen; Rui Li; Hui Peng; Mo Zhou; Rui-Xue Leng; Yin-Guang Fan; Jin-Hui Tao; Hai-Feng Pan; et al. (Inflammation Research, 2013)

Cloning, characterization and expression of the LECT2 gene in grass carp - Tian Yuan; Chuang Li; Ji-Rui Gu; Yue-Jun Fu; Heng Xu (Fish Physiology and Biochemistry, 2013)

Local responses to macro development policies and their effects on rural system in China’s mountainous regions: the case of Shuanghe Village in Sichuan Province - Yu-rui Li; Yan-sui Liu; Hua-lou Long; Jie-yong Wang (Journal of Mountain Science, 2013)
China has promulgated a series of policies including the Western Development Program, the Grain for Green Project, agricultural support policies and building a new countryside strategy to eliminate east-west differences and urban-rural disparities since the late 1990s. This paper gives a holistic examination on local responses to the four typical macro socio-economic development policies and their effects on rural system based on a case study of a mountainous village in southern Sichuan Province. The results showed that the policies have not moved the case study village from its historically marginal status. To some extent, its socio-economic situation might have been worsened by accelerated out-migration of the youth, loss of agricultural land due to afforestation and industrial plants, increased fire hazard due to afforestation and reforestation, increased environmental pollution due to industrial enterprises attracted to the village and a steep decline in agricultural production due to loss of and inefficient use of cultivated land. Factors causing local villages’ dilemmas include the nonuniformity of actors’ objectives, finiteness of villagers’ abilities, and the imperfect incentive and restraint mechanism for local government’s activities under existing policy framework composed of uncoordinated one-size-fits-all policies. We suggest that China’s rural policy in the new period should gradually shift from a sectoral to a place-based one, from top-down incentives to the development of bottom-up projects, and fully recognize the diversity of rural space, so as to lift local capacities and make good use of the knowledge shared by different actors. Moreover, it is also necessary to integrate the various sectoral policies, and improve the interministerial and interdepartmental coordination of rural policies at regional and local levels.

Involvement of dopamine D2 receptors activation in ischemic post-conditioning-induced cardioprotection through promoting PKC-ε particulate translocation in isolated rat hearts - Jun Gao; Jin Guo; Hongxia Li; Shuzhi Bai; Hong Li; Bo Wu; Lina Wang; Yuhui Xi; Ye Tian; Guangdong Yang; Rui Wang; Lingyun Wu; et al. (Molecular and Cellular Biochemistry, 2013)

Effect of total dissolved gas supersaturated water on early life of David’s schizothoracin (Schizothorax davidi) - Rui-feng Liang; Bo Li; Ke-feng Li; You-cai Tuo (Journal of Zhejiang University-SCIENCE B, 2013)

Complete disassociation of adult pancreas into viable single cells through cold trypsin-EDTA digestion - Dan Li; Shi-yun Peng; Zhen-wu Zhang; Rui-cheng Feng; Lu Li; Jie Liang; Sheng Tai; Chun-bo Teng (Journal of Zhejiang University-SCIENCE B, 2013)

Microdissection and painting of the Y chromosome in spinach (Spinacia oleracea) - Chuan-liang Deng; Rui-yun Qin; Ying Cao; Jun Gao; Shu-fen Li; Wu-jun Gao; Long-dou Lu (Journal of Plant Research, 2013)

Priming of Anti-Herbivore Defense in Tomato by Arbuscular Mycorrhizal Fungus and Involvement of the Jasmonate Pathway - Yuan Yuan Song; Mao Ye; Chuan You Li; Rui Long Wang; Xiao Chen Wei; Shi Ming Luo; Ren Sen Zeng (Journal of Chemical Ecology, 2013)

Hydrological Simulation by SWAT Model with Fixed and Varied Parameterization Approaches Under Land Use Change - Jinkang Du; Hanyi Rui; Tianhui Zuo; Qian Li; Dapeng Zheng; Ailing Chen; Youpeng Xu; C.-Y. Xu (Water Resources Management, 2013)

Effects of Vinasse and Press Mud Application on the Biological Properties of Soils and Productivity of Sugarcane - Shang-Dong Yang; Jun-Xian Liu; Jun Wu; Hong-Wei Tan; Yang-Rui Li (Sugar Tech, 2013)

Effects of Ethephon on Key Enzymes of Sucrose Metabolism in Relation to Sucrose Accumulation in Sugarcane - Ai-Qin Wang; Wen-Jing Huang; Jun-Qi Niu; Ming Liu; Li-Tao Yang; Yang-Rui Li (Sugar Tech, 2013)

An AFLP, SRAP, and SSR Genetic Linkage Map and Identification of QTLs for Fruit Traits in Pear (Pyrus L.) - Rui-ping Zhang; Jun Wu; Xiu-gen Li; M. Awais Khan; Hui Chen; Schuyler S. Korban; Shao-ling Zhang (Plant Molecular Biology Reporter, 2013)

High resource capture and use efficiency and prolonged growth season contribute to invasiveness of Eupatorium adenophorum - Wei-Bin Wang; Rui-Fang Wang; Yan-Bao Lei; Chao Liu; Li-Hong Han; Xiao-Dong Shi; Yu-Long Feng (Plant Ecology, 2013)

Re–Os molybdenite ages and zircon Hf isotopes of the Gangjiang porphyry Cu–Mo deposit in the Tibetan Orogen - Cheng-Biao Leng; Xing-Chun Zhang; Hong Zhong; Rui-Zhong Hu; Wei-De Zhou; Chao Li (Mineralium Deposita, 2013)

Effects of grazing on CO2 balance in a semiarid steppe: field observations and modeling - Xiaoming Kang; Yanbin Hao; Xiaoyong Cui; Huai Chen; Changsheng Li; Yichao Rui; Jianqing Tian; Paul Kardol; Lei Zhong; Jinzhi Wang; Yanfen Wang (Journal of Soils and Sediments, 2013)

Meso-Cenozoic extensional structures in the Northern Tarim Basin, NW China - Yue-Jun Li; Yan Zhao; Long-De Sun; Wen-Jie Song; Duo-Ming Zheng; Ya-Lei Liu; Dao-Xuan Wang; Jian-Feng Hu; Qi-Rui Zhang (International Journal of Earth Sciences, 2013)

A miR-570 binding site polymorphism in the B7-H1 gene is associated with the risk of gastric adenocarcinoma - Weipeng Wang; Fang Li; Yong Mao; Huan Zhou; Jing Sun; Rui Li; Cuiping Liu; Weichang Chen; Dong Hua; Xueguang Zhang (Human Genetics, 2013)

Treatment with exogenous hydrogen sulfide attenuates hyperoxia-induced acute lung injury in mice - Huai-Dong Li; Zhao-Rui Zhang; Qing-Xiang Zhang; Zhi-Chu Qin; Deng-Ming He; Jin-Song Chen (European Journal of Applied Physiology, 2013)

The presence of Genogroup II Norovirus in Retail Shellfish from Seven Coastal Cities in China - Li-ping Ma; Feng Zhao; Lin Yao; Xin-guang Li; De-qing Zhou; Rui-ling Zhang (Food and Environmental Virology, 2013)

A new cyclonerol derivative from a marine-derived fungus Ascotricha sp. ZJ-M-5 - Lei-Rui Xie; Dan-Yi Li; Zhan-Lin Li; Hui-Ming Hua; Pei-Le Wang; Xin Wu (Natural Product Research, 2013)

Cladosporium cladosporioides XJ-AC03, an aconitine-producing endophytic fungus isolated from Aconitum leucostomum - Kai Yang; Jie Liang; Qinfan Li; Xiangya Kong; Rui Chen; Yimin Jin (World Journal of Microbiology and Biotechnology, 2013)

Recombinant High Density Lipoprotein Nanoparticles for Target-Specific Delivery of siRNA - Mengjie Rui; Hailing Tang; Yan Li; Xiaohui Wei; Yuhong Xu (Pharmaceutical Research, 2013)

A novel Trichoderma species isolated from soil in Guizhou, T. guizhouense - Qi-Rui Li; Ping Tan; Yu-Lan Jiang; Kevin D. Hyde; Eric H. C. Mckenzie; Ali H. Bahkali; Ji-Chuan Kang; Yong Wang (Mycological Progress, 2013)

MicroRNAs-1614-3p gene seed region polymorphisms and association analysis with chicken production traits - Hong Li; Gui-Rong Sun; Ya-Dong Tian; Rui-Li Han; Guo-Xi Li; Xiang-Tao Kang (Journal of Applied Genetics, 2013)

Pelagibacterium nitratireducens sp.nov., A Marine Alphaproteobacterium Isolated from the East China Sea - Qipei Li; Yongle Xu; Keshao Liu; Lanlan Cai; Yingnan Fu; Jia Sun; Rui Zhang (Current Microbiology, 2013)

Selection and characterization of colorectal cancer cell-specific peptides - Han Wang; Caixia Ma; Rui Li; Yonge Guo; Yakun He; Xiaojing Wang; Yiwen Chen; Yingchun Hou (Biotechnology Letters, 2013)

Comparison of transcriptome under red and blue light culture of Saccharina japonica (Phaeophyceae) - Wen-Jun Wang; Fei-Jiu Wang; Xiu-Tao Sun; Fu-Li Liu; Zhou-Rui Liang (Planta, 2013)

Molecular cloning and functional analysis of a blue light receptor gene MdCRY2 from apple (Malus domestica) - Yuan-Yuan Li; Ke Mao; Cheng Zhao; Xian-Yan Zhao; Rui-Fen Zhang; Hua-Lei Zhang; Huai-Rui Shu; Yu-Jin Hao (Plant Cell Reports, 2013)

Comparative study of the interactions between ovalbumin and three alkaloids by spectrofluorimetry - Rui-qiang Wang; Yu-jing Yin; Hua Li; Yi Wang; Juan-Juan Pu; Rui Wang; Huan-jing Dou; Chuan-jun Song; Rui-yong Wang (Molecular Biology Reports, 2013)

Inhibition of autophagy enhances anticancer effects of bevacizumab in hepatocarcinoma - Xian-ling Guo; Ding Li; Kai Sun; Jin Wang; Yan Liu; Jian-rui Song; Qiu-dong Zhao; Shan-shan Zhang; Wei-jie Deng; Xue Zhao; Meng-chao Wu; Li-xin Wei (Journal of Molecular Medicine, 2013)

Upregulation of CBLL1 in rat brain cortex after lipopolysaccharide treated - Maohong Cao; Heyi Zheng; Xiang Tan; Wei Xu; Ying Rui; Lei Li; Xiaofei Liu; Guangfei Xu; Gang Cui; Jian Xu; Jianhua Cao; Kaifu Ke; et al. (Journal of Molecular Histology, 2013)

Overexpression of integrin-linked kinase (ILK) is associated with tumor progression and an unfavorable prognosis in patients with colorectal cancer - Rui Li; Baolin Liu; Hongzhuan Yin; Wei Sun; Jianqiao Yin; Qi Su (Journal of Molecular Histology, 2013)

Shrubs and species identity effects on the distribution and diversity of ground-dwelling arthropods in a Gobi desert - Feng-Rui Li; Ji-Liang Liu; Chang-An Liu; Qi-Jun Liu; Rui-Xue Niu (Journal of Insect Conservation, 2013)

Characterizing the interactions between polycyclic aromatic hydrocarbons and fulvic acids in water - Rui Lu; Guo-Ping Sheng; Yi Liang; Wei-Hua Li; Zhong-Hua Tong; Wei Chen; Han-Qing Yu (Environmental Science and Pollution Research, 2013)

Genomewide analysis of the chitinase gene family in Populus trichocarpa - CONG JIANG; RUI FANG HUANG; JIA LIANG SONG; MIN REN HUANG; LI AN XU (Journal of Genetics, 2013)

Antidepressant-like effect of flaxseed secoisolariciresinol diglycoside in ovariectomized mice subjected to unpredictable chronic stress - Xing Ma; Rui Wang; Xin Zhao; Chong Zhang; Jiao Sun; Jianxin Li; Lu Zhang; Tuo Shao; Lina Ruan; Liang Chen; Ying Xu; Jianchun Pan (Metabolic Brain Disease, 2013)

Thermus tengchongensis sp. nov., isolated from a geothermally heated soil sample in Tengchong, Yunnan, south-west China - Tian-Tian Yu; Ji-Cheng Yao; Hong Ming; Yi-Rui Yin; En-Min Zhou; Min-Jiao Liu; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Impact of the next-generation sequencing data depth on various biological result inferences - Rui Hou; ZhenXing Yang; MingHui Li; HuaSheng Xiao (Science China Life Sciences, 2013)

DNA polymerase beta promoter mutations affect gene transcription, translation and the sensitivity of esophageal cancer cells to cisplatin treatment - Tao Wang; Wenqiao Zang; Yunyun Ma; Min Li; Xiaoyan Xuan; Na Wang; Rui Wu; Yuebai Li; Ziming Dong; Guoqiang Zhao (Molecular Biology Reports, 2013)

Effect of PI3K gene silencing on growth, migration and related proteins expression of CD40 signal-mediated gastric cancer cells - Rui Li; Wei-Chang Chen; Xue-Qin Pang; Wen-Yan Tian; Wei-Peng Wang; Xue Guang Zhang (Molecular Biology Reports, 2013)

Association of the apolipoprotein M gene polymorphisms and serum lipid levels - Lynn Htet Htet Aung; Rui-Xing Yin; Dong-Feng Wu; Ting-Ting Yan; Qing Li; Jin-Zhen Wu; Wei-Xiong Lin; Cheng-Wu Liu; Shang-Ling Pan (Molecular Biology Reports, 2013)

The roles of ADIPOQ genetic variations in cancer risk: evidence from published studies - Yeqiong Xu; Bangshun He; Yuqin Pan; Ling Gu; Zhenlin Nie; Liping Chen; Rui Li; Tianyi Gao; Shukui Wang (Molecular Biology Reports, 2013)

Spatio-temporal reconstruction of air temperature maps and their application to estimate rice growing season heat accumulation using multi-temporal MODIS data - Li-wen Zhang; Jing-feng Huang; Rui-fang Guo; Xin-xing Li; Wen-bo Sun; Xiu-zhen Wang (Journal of Zhejiang University-SCIENCE B, 2013)

An approach for the critical coagulation concentration estimation of polydisperse colloidal suspensions of soil and humus - Mingyun Jia; Hang Li; Hualing Zhu; Rui Tian; Xiaodan Gao (Journal of Soils and Sediments, 2013)

Molecular cloning and characterization of SoNCED, a novel gene encoding 9-cis-epoxycarotenoid dioxygenase from sugarcane (Saccharum officinarum L.) - Chang-Ning Li; Manoj-Kumar Srivastava; Qian Nong; Li-Tao Yang; Yang-Rui Li (Genes & Genomics, 2013)

Litoribacillus peritrichatus gen. nov. sp. nov., isolated from coastal sediment of an amphioxus breeding zone in Qingdao, China - Rui Zhao; Shiqi Ji; Yan Wang; Tong Yu; Zhao Li; Bingyu Li; Xiaochong Shi; Xiao-Hua Zhang (Antonie van Leeuwenhoek, 2013)

A stepwise cloud shadow detection approach combining geometry determination and SVM classification for MODIS data - Rui Zhang; Donglian Sun; Sanmei Li; Yunyue Yu (International Journal of Remote Sensing, 2013)

Paroxetine up-regulates neurogenesis in hippocampus-derived neural stem cell from fetal rats - Zheng-wu Peng; Fen Xue; Hua-ning Wang; Rui-guo Zhang; Yun-chun Chen; Ying Wang; Li-yi Zhang; Juan Fan; Qing-rong Tan (Molecular and Cellular Biochemistry, 2013)

Screening level ecological risk assessment for synthetic musks in surface water of Lake Taihu, China - Guang-Hui Guo; Feng-Chang Wu; Hong-Ping He; Rui-Qing Zhang; Hui-Xian Li (Stochastic Environmental Research and Risk Assessment, 2013)

Expression profiles of Th17 pathway related genes in human systemic lupus erythematosus - Hai-Feng Pan; Rui-Xue Leng; Chen-Chen Feng; Xiang-Pei Li; Gui-Mei Chen; Bao-Zhu Li; Wang-Dong Xu; Song Guo Zheng; Dong-Qing Ye (Molecular Biology Reports, 2013)

Isolation and characterization of a stress responsive small GTP-binding protein AhRabG3b in peanut (Arachis hypogaea L.) - Jiong-Ming Sui; Rui Li; Qian-Cheng Fan; Lin Song; Chun-Hua Zheng; Jing-Shan Wang; Li-Xian Qiao; Shan-Lin Yu (Euphytica, 2013)

Meta-analysis of QTL associated with tolerance to abiotic stresses in barley - Wei-Tao Li; Chunji Liu; Ya-Xi Liu; Zhi-En Pu; Shou-Fen Dai; Ji-Rui Wang; Xiu-Jin Lan; You-Liang Zheng; Yu-Ming Wei (Euphytica, 2013)